Fármacos estabilizadores do humor regulam a expressão do sensor neuronal de cálcio 1 (NCS-1) - Luiz Alexandre Viana Magno (2012)
Mood stabilizers (MSDs) represent a class of drugs commonly prescribed for bipolar disorder (BD) treatment though the molecular mechanisms underlying their actions remain to be identified. The aim of this study was to evaluate the effect of the MSDs lithium (Li), valproate (VPA), lamotrigine (LTG) and carbamazepine (CBZ) on the levels of neuronal calcium sensor 1 (Ncs-1), a multifunctional protein has been involved in many neuronal functions such as survival and dopamine signaling. Furthermore, the biological impact of the Ncs-1 genetic disruption was investigated in mice and Caenorhabditis elegans as well. Treatment with a therapeutically relevant dose of Li and VPA for 4 weeks caused an increase in the level of Ncs-1 in mouse frontal cortex. Interestingly, this effect was abolished in Arr2 (beta-arrestin 2) and D2R (dopamine receptor type 2) knockout (KO) mice. Two inhibitors of Gsk3 or Mek1/2 (TDZD and U0126, respectively), recently identified targets of Li and VPA, but not histone deacetylase specific inhibitors, also increased the levels of Ncs-1 protein and gene expression both in vitro and in vivo. On the other hand, Gsk3overexpression strongly reduced Ncs-1 mRNA levels. Cycloheximide, an inhibitor of protein biosynthesis in eukaryotic organisms, was found to impair the TDZD or U0126-induced Ncs-1 expression. Then, we developed a luciferase reporter system to investigate how the Gsk3 and Erk1/2 inhibition regulate the Ncs-1 gene expression. However, no significant luciferase activity was found in transfected cells with the constructs of the Ncs-1 promoter. Furthermore, we also found significant changes in cerebral oxidative stress and energy metabolism, memory impairment and lack of the d-amphetamine-induced hyperlocomotion in Ncs-1 KO mice. We have found decreased levels of Ncs-1 in the frontal cortex of a d-amphetamine-based behavioral model of acute mania, however, one week VPA treatment restored both the behavior and the Ncs-1 levels. To our knowledge, this is the first report that has investigated the pharmacologic action of MSDs on Ncs-1 expression. Our data suggest that these drugs might exert their actions on Ncs-1 via Gsk3 and Erk inhibition. The finding that two widely prescribed mood stabilizers have a common action, the increased Ncs-1 protein expression in vitro and in vitro, raises the question of what the link is between the mechanisms of action of the mood stabilizers and Ncs-1 induction. It is also unclear whether Ncs-1 induction is involved in the mood-stabilizing effects of these drugs. Further studies will be needed to address these issues and the involvement of Ncs-1 in the pathogenesis of BD. In conclusion, the data obtained from this study identified Ncs-1, a protein that may play a role in psychiatric disorders, as a protein that is commonly induced by the two mood stabilizers, Li e VPA.